Renal function-adjusted safe contrast volume to prevent contrast-induced nephropathy and poor long-term outcomes in patients with chronic total occlusions undergoing cardiac catheterization. (23rd June 2015) - Liu, Yong; Liu, Yuan-hui; Chen, Ji-yan; Tan, Ning; Li, Hua-long; Luo, Jian-fang; Chen, Zhu-jun; Yu, Dan-qing; Li, Guang; Huang, Wen-hui; Xie, Nian-jin; He, Peng-cheng; et al.
Abstract: We aimed to evaluate the value of the contrast volume to creatinine clearance (V/CrCl) ratio for predicting contrast-induced nephropathy (CIN) and to determine a safe V/CrCl cut-off value to avoid CIN in patients with chronic total occlusions (CTOs) undergoing cardiac catheterization. We prospectively enrolled 728 consecutive patients with CTOs undergoing cardiac catheterization. Receiver-operator characteristic (ROC) curves were used to identify the optimal sensitivity for the observed range of V/CrCl. The predictive value of V/CrCl for CIN was assessed using multivariate logistic regression. Twenty-one patients (2.88%) developed CIN. There was a significant association between a higher V/CrCl ratio and CIN risk ( P < 0.001). ROC curve analysis indicated that a V/CrCl ratio of 2.76 was a fair discriminator for CIN (C-statistic = 0.77). After adjusting for other known CIN predictors, V/CrCl ratio >2.76 remained significantly associated with CIN (OR = 5.22; 95% CI = 1.65–16.53, P = 0.005) or worse long-term outcomes [death: hazard ratio (HR) = 2.72, 95% CI = 1.32–5.60, P = 0.007; major adverse clinical events: HR = 1.46, 95% CI = 1.03–2.06, P = 0.034]. A V/CrCl ratio >2.76 was a predictor of CIN and was independently associated with poor long-term outcomes from our data.